+0  
 
0
112
1
avatar+148 

x^2 - 3x - 10 = 0

x^2 - 8x = 0

(x + 3)(2x - 1) = 0

x^2 = 4

x^2 = 10x - 25

2x^2 - 8x - 8 = -8

HeyxJacq  Feb 15, 2018
 #1
avatar+87572 
+2

x^2  -  3x  - 10  = 0     factor

(x - 5)(x +2) =  0      

Set each factor to 0 and solve for x  and we have that  x  = 5  or  x = -2

 

x^2 - 8x = 0

x( x - 8)  =  0

Set each factor to 0 and solve for x  and we have that  x  = 0  or  x = 8

 

(x + 3)(2x - 1) = 0

This is already factored

 

x +  3  = 0                             2x   -  1  =    0

   - 3     -3                                    +  1     + 1

x   =  -3                                  2x          = 1          divide both sides by 2

                                                x      =  1/2

 

 

x^2  = 4       subtract 4 from both sides

x^2  - 4  =  0    factor

( x + 2)  ( x - 2)  = 0

Settting each factor to 0 and solving and we have that   x = -2  or x  = 2

 

x^2 = 10x - 25       subtract  10x from both sides, add 25 to both sides

x^2 - 10x + 25  = 0    factor

(x - 5) ( x - 5)  =  0

Settting each factor to 0 and solving and we have that   x = 5   ( one solution )

 

2x^2 - 8x - 8 = -8    add 8  to both sides

2x^2  -  8x  =  0      factor

2x ( x - 4)  =  0  

Set each factor to 0 and solve and   x  =  0   or  x = 4

 

 

 

cool cool cool

CPhill  Feb 15, 2018

18 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.